2019
DOI: 10.1002/ece3.5818
|View full text |Cite
|
Sign up to set email alerts
|

Flight responses of eastern gray kangaroos to benign or harmful human behavior

Abstract: Globally, wilderness is being converted for rural and agricultural land use. In countryside landscapes, many habitat structures remain intact, providing suitable habitat for wildlife species that can accurately assess novel risks and develop tolerance to benign disturbances. Associative learning that promotes avoidance and also facilitates desensitization to benign disturbance is key to persisting in these landscapes. Conversely, learning to distinguish and avoid negative interactions with humans, like hunting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…This probably leads to an increase of the perceived risk from humans. Behavioral responses to human activity, such as increased FID and escape distance, are found in studies in various species (Austin & Ramp, 2019;de Boer et al, 2004;Holmern et al, 2016). However, few studies have shown direct effect on flight behavior of onset of hunting season.…”
Section: Flight Responsementioning
confidence: 99%
“…This probably leads to an increase of the perceived risk from humans. Behavioral responses to human activity, such as increased FID and escape distance, are found in studies in various species (Austin & Ramp, 2019;de Boer et al, 2004;Holmern et al, 2016). However, few studies have shown direct effect on flight behavior of onset of hunting season.…”
Section: Flight Responsementioning
confidence: 99%
“…Whether animals tolerate or avoid human disturbance is likely to depend on the nature of their interactions with people. For example, eastern gray kangaroos ( Macropus giganteus ) flee more readily from humans in areas with higher hunting pressure, compared to those in areas with a higher density of tourists and other forms of non-lethal disturbance ( Austin and Ramp, 2019 ). Conversely, animals may approach humans in areas where this behavior is actively rewarded: Barbary macaques ( Macaca sylvanus ) appear to spend more time using roadside habitat where they are provisioned by tourists, especially at times of higher tourist activity and when natural food sources become scarce ( Waterman et al, 2019 ).…”
Section: Variation In Responses To Humansmentioning
confidence: 99%
“…Though in rare cases, populations forced to share habitats with humans, such as leopards (Panthera pardus) in Mumbai, India, develop particular strategies like adjusting their daily time budget and prey selection to survive (Braczkowski et al, 2018). Additionally, some animal species adopted different strategies and have different destinies under different human disturbances, depending on the type and intensity of disturbances (Austin & Ramp, 2019;Jahren et al, 2020;Murdoch et al, 2016).…”
mentioning
confidence: 99%